Capacidade institucional dos municípios da região do Alto Paranaíba - MG - Silva, Edson Arlindo (2009)
The thesis´s main argument is that the bigger the population´s knowledge about the local institutions - its roles and functions - bigger are the possibilities of more civic engagement, the social capital and the bigger are the odds to effect the society´s public administration. All of those aspects together would create what we call Institutional Capacity. The presence and appropriate operation of those institutions in a city become a decisive condition for the local sustainable development since they can express the primordial elements´ manifestations towards life in society such as power decentralization, group values, social trust, rules and laws, democratic participation and civic acts. The understanding of Alto Paranaíba cities´ institutional capacity showed the potentialities and limitations found at the region´s public and private institutions. The research in three cities (Patos de Minas, Estrela do Sul and Santa Rosa da Serra) showed the population´s perception and evaluation towards the local institutions. The results presented show a reasonable rate of the population´s knowledge towards local institutions. Considering all above, Patos de Minas shows a great institutional capacity to promote its own sustainable development. This conclusion reinforces positively the result found at ZEE-MG of favorable capability for this city. In Estrela do Sul it became visible that the lack of institutions that were present in Patos de Minas had a negative effect on the institutional capacity of that city. The developments of that kind of relationship may vary a lot from region to region, but the results show similar aspects related to the limited practice of citizenship, the limited ability of the population to act collectively and the practice of a patrimonial public administration. In Santa Rosa da Serra, that situation is dramatic because the city has a low institutional capacity, revealed by both the ZEE-MG results when considering this city´s social potentiality too precarious and the results of a public opinion pool, which features the accentuated rate of institutional liability and typical ills off a patrimonial public administration.